Screening of novel 3α5β-neurosteroids for neuroprotective activity against glutamate- or NMDA-induced excitotoxicity. Issue 189 (May 2019) - Smidkova, Marketa; Hajek, Miroslav; Adla, Santosh Kumar; Slavikova, Barbora; Chodounska, Hana; Matousova, Marika; Mertlikova-Kaiserova, Helena; Kudova, Eva
Graphical abstract: Highlights: 3α5β-Neurosteroids suppress both glutamate- and NMDA-induced excitotoxicity. Ca2+ entry and consequent ROS release and caspase-3 activation attenuated. 3α5β-Neurosteroids have better neuroprotective properties than memantine. Potential cytotoxic effect of neurosteroids both time and concentration dependent. Abstract: A broad variety of central nervous system diseases have been associated with glutamate induced excitotoxicity under pathological conditions. The neuroprotective effects of neurosteroids can combat this excitotoxicity. Herein, we have demonstrated the neuroprotective effect of novel steroidal N -methyl-D-aspartate receptor inhibitors against glutamate- or NMDA- induced excitotoxicity. Pretreatment with neurosteroids significantly reduced acute L-glutamic acid or NMDA excitotoxicity mediated by Ca 2+ entry and consequent ROS (reactive oxygen species) release and caspase-3 activation. Compounds6 (IC50 = 5.8 μM), 7 (IC50 = 12.2 μM), 9 (IC50 = 7.8 μM), 13 (IC50 = 1.1 μM) and16 (IC50 = 8.2 μM) attenuated glutamate-induced Ca 2+ entry more effectively than memantine (IC50 = 18.9 μM). Moreover, compound13 shows comparable effect with MK-801 (IC50 = 1.2 μM) and also afforded significant protection without any adverse effect upon prolonged exposure. This drop in Ca 2+ level resulted in corresponding ROS suppression and prevented glutamate-induced caspase-3 activation. Therefore, compound13 has great potential for development into a therapeutic agent for improving glutamate-related nervous system diseases.